Qiwamah: A Normative Qur’anic Study on the Relations of Husband, Wife, and Mother - Amin, Ahmad Misbakhul; Nisa', Saidatun; Saifuddin, M. Afiq (Martabat: Jurnal Perempuan dan Anak, 2025)
Domestic conflict frequently emerges when two significant female figures—the mother and the wife—share a household. The root of such tension often lies in the husband’s inability to exercise effective leadership within the family. While the Qur’an presents a normative framework of leadership that can be applied domestically, its implementation remains complex. This study seeks to examine the relationship between mothers and wives through the lens of Qur’anic leadership, with a specific focus on the interpretive framework proposed by Yusuf Qardhawi’s al-Dilālah model. The analysis yielded three major findings. First, Qur’anic verses concerning devotion to parents, obligations to wives, and leadership responsibilities can be actualized flexibly and dynamically according to context. Second, devotion to mothers is obligatory; however, the authority of QS. al-‘Ankabūt [29]:8 (commanding filial piety) may, in certain circumstances, be reframed by QS. al-Nisā’ [4]:19 (commanding benevolent treatment toward wives). This insight is reinforced by psychological perspectives on motherhood. Third, while mothers retain the right to receive financial support from their children, the responsibility to provide for and care for one’s wife takes precedence as part of the husband’s greater leadership obligations.